Toeing the line between regeneration and fibrosis - Jou, Vivian; Lehoczky, Jessica A. (Frontiers in Cell and Developmental Biology, 2023)
Understanding the remarkable capacity of vertebrates to naturally regenerate injured body parts has great importance for potential translation into human therapeutic applications. As compared to other vertebrates, mammals have low regenerative capacity for composite tissues like the limb. However, some primates and rodents can regenerate the distal tips of their digits following amputation, indicating that at least very distal mammalian limb tissues are competent for innate regeneration. It follows that successful digit tip regenerative outcome is highly dependent on the location of the amputation; those proximal to the position of the nail organ do not regenerate and result in fibrosis. This distal regeneration versus proximal fibrosis duality of the mouse digit tip serves as a powerful model to investigate the driving factors in determining each process. In this review, we present the current understanding of distal digit tip regeneration in the context of cellular heterogeneity and the potential for different cell types to function as progenitor cells, in pro-regenerative signaling, or in moderating fibrosis. We then go on to discuss these themes in the context of what is known about proximal digit fibrosis, towards generating hypotheses for these distinct healing processes in the distal and proximal mouse digit.